VELOCITY CHANGES ANALYSIS DISPLACEMENT DATA USING GNSS (GLOBAL NAVIGATION SATELLITE SYSTEM) IN JATI GEDE DAM - Haryati, Aning - (Indonesia University of Education, 2017)
Jati Gede Dam is located around the border of Sumedang-Majalengka region in West Java province. Jati Gede Dam provides several benefits such as for irrigation, hydropower, tourism and fish farming. Dam can also trigger the potential a disaster, especially in the water impounding process. The process of water impounding in the dam has the potential to cause earthquake disaster. The effect of water impounding potentially adds stress accumulation in the dam area so that it can cause earthquakes. Therefore, a research on strain change due to the water impounding in Jati Gede dam is needed. The method used in the research is by GPR survey. Result from GPS observation processed to generate displacement value of GPS observation point, and strain changes from the point that formed grid strain. Based on deformation analysis the effect of water impounding to the strain around Jati Gede Dam can be obtained. Development in this thesis is by using and additional method namely Kinematic PPP to see the different pattern of earth tide phenomenon around the dam which were represented by several GPS station. These results indicate a change of velocity direction in the area around Jati Gede dam. This change can be analyzed for the station near the dam as JTG1 station, jtg2, CSUM, 0355, BDK2, CJR6, and MJLK. BDK2 campaign point leads toward the Southwestern, CJR6 displacements from the Southwest to the North, MJLK displacements from Southeast to the Northwest, and 0355 displacements from Southeast to the North. JTG1 GPS station point tends to lead toward the Southwestern and JTG2 GPS station leads toward the North with 0355 GPS station. CSUM in Sumedang displacements from Northwest to the East. This change can be analyzed for the station near the dam such as JTG1, JTG2, CSUM, 0355, BDK2, CJR6, and MJLK as result of the process of water filling in Jati Gede dam.